Carbon Sequestration Assessment of Selected Campus Champion Trees - Chi, Yeong Nain; Bardsley, James S; Bishop, Tracie J (Journal of Forests, 2020)
This study aims to quantify the unique score of selected champion trees on the University of Maryland Eastern Shore (UMES) main campus. Individual trees that are evaluated as “champions” of their species are measured for their trunk’s diameter at breast-height, overall tree height, and average crown spread to calculate their total score. Based on each specimen’s total score, selecting the top 20 champion trees provides data that is beneficial in developing a UMES campus tree map using geospatial technology. Furthermore, finding the carbon sequestered value and emissions-storage amount per tree is a targeted topic for the next step in this study. This study also provides a pilot direction for UMES to value its forested regions, to maintain these colossal trees, and to help the campus reach its sustainability goals. Given the relationship between tree size and efficiency of carbon sequestration demonstrated here, additional studies to test the hypothesis that some open grown tree species gain greater girth in a shorter period of time when compared to forest-grown specimens are encouraged to aid in tree selection.